(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
The proper functioning of human immune system is essential for organism survival against infectious, toxic and oncogenic agents. Immunomodulators are natural or synthetic materials that regulate the immune system and induce innate and adaptive defense mechanisms. These substances are classified into two types, immunostimulants and immunosuppressants. Immunostimulants can enhance body’s resistance against various infections through increasing the basal levels of immune response. These agents could increase the oxidative activity of neutrophils, augment engulfment activity of phagocytic cells and stimulate cytotoxic cells as necessary defense mechanisms. The immunostimulants are classified on the basis of origin and mode of action such as bacterial products, complex carbohydrates, vaccines, cytokines, immunoenhancing drugs, nutritional factors, animal extracts, and plant extracts. The link between immune system with diet, exercise, sleep, stress, microbial exposure, alcohol, water,hygiene are found to influence the immune response to a greater extent. Immunostimulants and some immunity enhancing nutrients improve the functioning of the immune system.